2005
DOI: 10.1007/s00167-004-0599-0
|View full text |Cite
|
Sign up to set email alerts
|

Accuracy and initial stability of open- and closed-wedge high tibial osteotomy: a cadaveric RSA study

Abstract: We analyzed the difference in angle-correction accuracy and initial stability between open-wedge (OWO) and closed-wedge tibial valgus osteotomy (CWO). Five fresh-frozen pairs of human cadaver lower limbs were used; their bone mineral density (BMD) was measured with DEXA and a planned 7 degrees valgus osteotomy was performed, either with an open (right knees) or closed (left knees) technique. All knees for osteotomy were fixed with a rigid locked plate. In OWO, tricalcium phosphate (TCP) wedges were inserted. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
22
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 31 publications
(24 citation statements)
references
References 16 publications
0
22
0
Order By: Relevance
“…We aimed to evaluate the intra-operative imaging in one type of surgery; the open wedge valgus HTO, and compared it with the were evaluated as not to bias the results by using different operating techniques and set-ups, and also because the postoperative loss of correction has been shown to differ between open and closed wedge osteotomies [15,16]. We aimed to evaluate the final radiographic outcome after placing the intra-operative mechanical axis on the lateral tibial eminence and to evaluate whether there is a loss of correction in the postoperative phase.…”
Section: Introductionmentioning
confidence: 99%
“…We aimed to evaluate the intra-operative imaging in one type of surgery; the open wedge valgus HTO, and compared it with the were evaluated as not to bias the results by using different operating techniques and set-ups, and also because the postoperative loss of correction has been shown to differ between open and closed wedge osteotomies [15,16]. We aimed to evaluate the final radiographic outcome after placing the intra-operative mechanical axis on the lateral tibial eminence and to evaluate whether there is a loss of correction in the postoperative phase.…”
Section: Introductionmentioning
confidence: 99%
“…Osteotomies fixated with these plates offer superior initial stability compared to other medial fixation plates and equal stability compared to similar plates used for CW-HTO (Gaasbeek et al 2005, Agneskirchner et al 2006). With these implants, immediate full weight bearing appears to be possible (Takeuchi et al 2008, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Many HTO implants have been designed and traditionally, cadaver knee [5,6] and synthetic bone studies [7][8][9] have been used to investigate the primary stability of different plate designs. These studies have shown that longer plates with locking screws provide higher stability in both compression [5,7,9] and torsion [9] than shorter plates.…”
Section: Introductionmentioning
confidence: 99%